Peluang Perbaikan Varietas Lokal Padi Gogo Pasaman Barat - Syahrul Zen; Abdul Aziz Syarif (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2013)
Local varietyis the major component in upland rice cultivation as well asbreeding material in variety improve-ment. Local upland ricevarieties have been adapted to specific location, preferred andadopted by farmers although they are late in maturity. Thesereasons make it majority of farmers in West Pasaman District(West Sumatra) still cultivate local upland rice varieties. Toknow the yield potential and agronomic characters of widelycultivated of upland rice in West Pasaman District, a varietytrial conducted in 2010. Five local varieties and one improvevariety planted a Randomized complete block arrangementwith three replications. Observa-tion conducted on agronomiccharacters and yield and yield components. The results showedthat local variteies were tall (153-171 cm) and late maturity(130-157 days). The local varieties also showed higher numberof spikelet/panicle (249-454) lighter 1.000 grains weight (<20g) and higher yield than improved variety (4.27-5.51 comparedto 2.85 t/ha). In general all plant characters showed highheritability estimate (except number of productive tiller/hillr).High estimated of genetic variation coefficient and geneticadvance were shown on number of grain per panicle. Based onthese genetic parameters, selection at early generation for highyield can conducted on number of grain per panicle.